Leadership: a key element in organizational success - Baena-Ordosgoitia, Angie (EFIM Ediciones, 2019)
The common dream on all companies is to fnd the secret formula that can guarantee them a permanent spot on the market and results above the expected ones. to achieve this is fundamental to have the required resources within the company, not only the economical and technological, specially the human resource needs to be taken into account, this resource needs to have the required knowledge and needs to be committed to reach the objectives on a constant basis. These objectives can only be achieved when all the resources are aligned with the organizational philosophy. The easiest way to reach this result is with a well rounded management. This revision analyzes Niccolò Machiavelli’s The Prince, focused on the practice that, as leaders, people that run companies need to have, their characteristics, the diﬀerent levels and styles of management based on leadership, the tollgates and follow ups as a key piece on target achievement and company goals, as well as the importance that all participants have on the fulfllment of these.